Stress From Caregiving - Donna Davis; Suzanna Smith (EDIS)
FAR-6000, a 2-page transcript of the radio broadcast by Donna Davis and Suzanna Smith, lists some ways that caregivers can provide quality care to their relatives by providing quality care to themselves. Includes links to sounds files of the radio broadcast. Published by the UF Department of Family Youth and Community Sciences, May 2006.